Electronic pillboxes (MEMS) to assess the relationship between medication adherence and blood pressure control in primary care - Zeller, Andreas (Informa Healthcare, 2007)
OBJECTIVE: To investigate the relationship between blood pressure and medication adherence using electronic pillboxes (MEMS). SETTING: Five general practices in Bristol, UK. SUBJECTS: A total of 239 individuals with a clinical diagnosis of hypertension and being prescribed at least one blood pressure-lowering medication. Participants were asked to use the electronic pillbox as their drug bottle for at least one month. MAIN OUTCOME MEASURES: “Timing adherence” (correct inter-dose intervals) as measured through MEMS and systolic (SBP) and diastolic (DBP) office blood pressure. RESULTS: Mean (±SD) timing adherence was 88% (±17),>80% in 175 (73%), and less than 50% in 11 (5%) participants. Adherence was monitored for a mean of 33 (±6) days. Mean (±SD) SBP was 147.9±19.1 mmHg and DBP 82.3±10.1 mmHg. There was no evidence to suggest that timing adherence was associated with SBP or DBP (overall correlation coefficients −0.01 and −0.02 respectively). According to current guidelines, about one in four of all participants had controlled SBP (only 6% of diabetic patients). DBP was under control in 66% of the individuals. CONCLUSIONS: No relationship between adherence and blood pressure in patients with hypertension recruited from primary care was found. Average timing adherence measured by electronic monitors was high (88%) and blood pressure was controlled in a minority of patients. Our findings suggest that in terms of poor blood pressure control pharmacological non-response to or insufficient intensity of blood pressure-lowering medication might be more important than poor adherence to antihypertensive drug therapy.